If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1A + 2B + 3C = 30 Solving 1A + 2B + 3C = 30 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-2B' to each side of the equation. 1A + 2B + -2B + 3C = 30 + -2B Combine like terms: 2B + -2B = 0 1A + 0 + 3C = 30 + -2B 1A + 3C = 30 + -2B Add '-3C' to each side of the equation. 1A + 3C + -3C = 30 + -2B + -3C Combine like terms: 3C + -3C = 0 1A + 0 = 30 + -2B + -3C 1A = 30 + -2B + -3C Divide each side by '1'. A = 30 + -2B + -3C Simplifying A = 30 + -2B + -3C
| 2(x+7)-7=9 | | 5-x=3(x-1) | | -2(x+3)=20 | | 24-10x=9 | | 5x-4y=17 | | n^4-n^3-n+1=0 | | -2x+3y=52 | | 25x=125x+2 | | 8z+9-7z-2= | | X-3=2x+12 | | -5+x=9 | | 28=7x+28 | | -4x+4=2 | | -25=10x-5 | | 3x-4+9=5-6x | | 2(3x-1)=58 | | x^2-60x-900=0 | | 15x+9=54 | | 6x-4x^2-1=0 | | 1.4x+10=2 | | -1+6x-4x^2=0 | | 36=9x-9 | | 12x+9y-(12x+14y)=6 | | 7x-12=2x+18 | | y-3=-24 | | 9z^2+6z-8=0 | | (x+6)+3=30 | | x+13=-5 | | 4x+6x-2=18 | | 3b+17=11x-13 | | t^2-6t+31=0 | | x+5x=10 |